Implikasi Hukum Terhadap Penetapan Tersangka Kembali Setelah Dibatalkan Oleh Putusan Praperadilan - Momy Tahir; Ramdhan Kasim; Robby W. Amu (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This study aims to find out about . What are the legal provisions for determining suspects as pretrial objects in criminal law and b What are the legal implications for re-determination of suspects after being canceled by a pretrial decision. The data collection method in this study was carried out by literature study, which is a way of collecting data by searching and studying library materials (literature, research results, scientific magazines, scientific bulletins, scientific journals, etc.). Legal materials are collected through inventory procedures and identification of laws and regulations, as well as classification and systematization of legal materials according to research problems. Therefore, the data collection technique used in this study was a literature study. The results of the study show that pretrial is a new thing in the life of law enforcement in Indonesia, has a goal to be upheld and protected, namely protecting the rights of suspects at the level of investigation and prosecution or preventing the arbitrariness of law enforcement officials against someone who is undergoing a legal process and To guarantee the protection of human rights and for law enforcers to carry out their duties consistently, the Criminal Procedure Code establishes a new institution called pretrial. Seeing the contents of the decision as referred to in Article 82 paragraph (3) of the Criminal Procedure Code, that there are 3 (three) types of implementation of pretrial decisions: committing certain acts, paying an amount of money and providing rehabilitation. The legal basis for pretrial authority in deciding the suspect's determination is found in the Constitutional Court (MK) decision No. 21/PUU-XII/2014 which states that the determination of the status of a suspect is included in the object of pretrial and also in its ruling that Article 77 of the Criminal Procedure Code is contrary to the 1945 Constitution and does not have binding legal force as long as the pretrial is not interpreted including determination of suspects, searches , and confiscation. Meanwhile, the background to the addition of pretrial authority in deciding the determination of the suspect is that the determination of the suspect's status is the end result of the investigation activities carried out which are none other than the object of pretrial. Criminal acts after the status of the determination of the suspect is declared invalid in the pretrial decision are basically still valid. Examination in pretrial cases is only in the administrative area of ​​the investigative process. Often the Pretrial decision which cancels the determination of the suspect by the investigator, is based.